Exploring Lexical and Contextual Meaning in Olivia Rodrigo’s Song Lyrics in Sour Album - Ramadani, Tri; Anwar, Syahlafiya; Wardoyo, Cipto (LITERA : Jurnal Bahasa Dan Sastra, 2025)
This research aimed to explore the lexical and contextual meanings in Olivia Rodrigo’s song lyrics from her album Sour. Using a qualitative descriptive approach, this study analyzed how Olivia Rodrigo’s word choice and context convey deep emotions and messages through literal and contextual meanings. The results of this study revealed how simple yet emotionally charged language is used to describe complex feelings and experiences. Songs such as Brutal, Jealousy, Jealousy, Traitor, and Hope Ur Ok feature themes of love, self-doubt, jealousy, social criticism, and personal growth. Song lyrics are seen as a language-based art form that not only relies on the beauty of words but is also loaded with emotional and social meaning. By analyzing word choice and context, this research also highlighted the way Olivia Rodrigo makes music a valuable tool for language learning and cultural analysis, enriching the understanding of emotional and linguistic expression in music. The research concluded that the lyrics in Sour analyzed through Literal and Contextual depict the narrative of modern life by using simple but powerful language, creating a deep emotional resonance with the listener.